Longterm prognosis of combined hepatocellular carcinoma‐cholangiocarcinoma following liver transplantation and resection. Issue 3 (March 2017) - Jung, Dong‐Hwan; Hwang, Shin; Song, Gi‐Won; Ahn, Chul‐Soo; Moon, Deok‐Bog; Kim, Ki‐Hun; Ha, Tae‐Yong; Park, Gil‐Chun; Hong, Seung‐Mo; Kim, Wan‐Jun; Kang, Woo‐Hyoung; Kim, Seok‐Hwan; et al.
Abstract : Combined hepatocellular carcinoma–cholangiocarcinoma (cHCC‐CC) is a rare disease. We investigated the clinicopathological features of cHCC‐CC and compared the longterm outcomes following liver transplantation (LT) and hepatic resection (HR). We identified 32 LT patients with cHCC‐CC through an institutional database search. The HR control group (n = 100) was selected through propensity score‐matching. The incidence of cHCC‐CC among all adult LT patients was 1.0%. Mean patient age was 53.4 ± 6.7 years, and 26 patients were male. Thirty patients had hepatitis B virus infection. All patients of cHCC‐CC were diagnosed incidentally in the explanted livers. Mean tumor diameter was 2.5 ± 1.3 cm, and 28 patients had single tumors. Tumor stage was stage I in 23 and II in 9. Concurrent hepatocellular carcinoma (HCC) was detected in 12 patients with stage I in 5 and II in 7. Mean tumor diameter was 1.9 ± 1.2 cm, and 5 had single tumors. Tumor recurrence and survival rates were 15.6% and 84.4% at 1 year and 32.2% and 65.8% at 5 years, respectively. Patients with very early stage cHCC‐CC (1 or 2 tumors ≤ 2.0 cm) showed 13.3% tumor recurrence and 93.3% patient survival rates at 5 years, which were significantly improved than those with advanced tumors ( P = 0.002). Tumor recurrence and survival rates did not differ significantly between the LT and HR control groups ( P = 0.22 and P = 0.91, respectively); however, postrecurrence patient survival did ( P = 0.016). In conclusion, cHCC‐CC is rarely diagnosed following LT, and one‐third of such patients have concurrent HCC. The longterm posttransplant prognosis was similar following LT and HR. Very early cHCC‐CC resulted in favorable posttransplant prognosis, thus this selection condition can be prudently considered for LT indication. Liver Transplantation 23 330–341 2017 AASLD .